2005
DOI: 10.2220/biomedres.26.61
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stretching stress on the muscle contraction proteins of skeletal muscle myoblasts

Abstract: Several studies have reported that growth and differentiation of cultured myoblasts can be facilitated by applying appropriate mechanical stimulus. However, the effects of mechanical stimulus on the characteristics of muscle fi bers have not yet been fully elucidated. In this study, we gave mechanical stress to C2C12 cells, which were myoblasts derived from mice skeletal muscle. The following myosin heavy chain (MHC) isoforms were investigated in order to clarify muscle characteristics: MHC-2b, 2d and 2a, all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 22 publications
3
31
0
Order By: Relevance
“…This result is consistent with the findings of a study by Sakiyama et al 13) demonstrating the enhancement of myoblast differentiation induced by extending stimulation as observed by electron microscopy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is consistent with the findings of a study by Sakiyama et al 13) demonstrating the enhancement of myoblast differentiation induced by extending stimulation as observed by electron microscopy.…”
Section: Discussionsupporting
confidence: 93%
“…Naumann and Pette administered electrical stimulation to cells obtained from rat hind leg and soleus muscles via culture medium and reported its effects on expression of myosin heavy-chain (MyHC) isoforms 10) . Sakiyama et al reported differences in myoblast proliferation and muscle fiber characteristics induced by extending stimulation 13) . Sakuraba et al examined the effects of magnetic stimulation of rat hind leg muscles on expression of mRNA by comparing stimulation and control groups 14) .…”
Section: Introductionmentioning
confidence: 99%
“…Culture medium containing 2% FBS was used after allowing cells to adhere to the membrane for 1 day. The cells were then stretched according to the method of Sakiyama et al (21).…”
mentioning
confidence: 99%
“…The stretch rate was established using the stretch rate setting method of a Flexercell ® strain unit. Since Sakiyama et al (21) performed an experiment at a stretch rate of 0.5/sec in a previous report, this condition was adopted as the standard. This rate represents the distance of membrane movement per second: 1/sec indicates that a membrane stretches from a stationary state then relaxes to return to the original state in 1 second.…”
mentioning
confidence: 99%
See 1 more Smart Citation